Impact of an Early-Career Shock on Intergenerational Mobility - Kaila, Martti; Nix, Emily; Riukula, Krista (Journal of Labor Economics, 2025)
Children’s and parents’ incomes are highly correlated, yet little is known about how early-career shocks contribute to this correlation. This paper focuses on a consequential labor market shock: job loss. We document three new results. First, adult children born into the bottom 20% of the income distribution have double the unemployment following job loss compared with those from the top 20% and 154% higher earnings losses. Second, this increases the rank-rank correlation 30% for those impacted. Third, richer parents provide career opportunities to their adult children after job loss, consistent with advantages from wealthy parents persisting well into adulthood.